THE INFLUENCE OF SERVICE QUALITY, PRICE, AND PROMOTION ON CUSTOMER SATISFACTION TOKOPEDIA - Noviyanti, Risa; Kurnianingsih, Heny (Universitas Ibn Khaldun Bogor, 2023)
This study intends to determine the effect of service quality, price, and promotion on Tokopedia customer satisfaction in a case study of STIE Surakarta students. The variables of this study are Service Quality (X1), Price (X2), Promotion (X3), and Customer Satisfaction (Y). The sampling technique used is Simple Random Sampling by taking the total population sample. With an error rate of 5%, the number of samples is 165. So the sample in this study is 165 respondents. The data analysis technique uses multiple linear analysis. The test was calculated using SPSS 25.0 for windows. Consecutive data processing is carried out by conducting validity and reliability tests, normality tests, multicollinearity tests, heteroscedasticity, calculating the coefficient of determination, and t-test.